Microstructure and corrosion properties of the low-density single-phase compositionally complex alloy AlTiVCr. (1st April 2018) - Qiu, Y.; Thomas, S.; Gibson, M.A.; Fraser, H.L.; Pohl, K.; Birbilis, N.
Highlights: The corrosion characteristics of a CCA-AlTiVCr is presented. AlTiVCr showed superior corrosion resistance in 0.6 M NaCl compared to 304SS. Un-oxidised metal species were detected in the passive layer formed upon AlTiVCr. Un-oxidised metal in the film may serve to enhance passivity of AlTiVCr. Abstract: Compositionally complex alloys (CCAs) possess unique microstructures and passive films, which need to be studied to contribute to fundamental understanding of corrosion in such alloys. Herein, we report the corrosion characteristics of a single phase CCA, AlTiVCr, designed to have a low-density (5.06 g cm −3 ) relative to other CCAs. AlTiVCr was found to exhibit excellent corrosion resistance in 0.6 M NaCl (with Epit > 1.27 VSCE ). A passive layer comprising of mixed metallic oxides interspersed with un-oxidised metal species was detected upon this CCA using X-ray photoelectron spectroscopy, which was hypothesised to contribute to excellent corrosion resistance.